Cervical cytological abnormalities and HPV infection in perinatally HIV-infected adolescents - J. Ananworanich; W. Prasitsuebsai; S.J. Kerr; R. Hansudewechakul; N. Teeratakulpisarn; K. Saisawat; R. Ramautarsing; J. Achalapong; K. Pussadee; S. Keadpudsa; T. Mackay; T. Pankam; et al. (Elsevier, 2015)
Background: Behaviourally HIV-infected adolescent females are at higher risk for abnormal cervical cytology and HPV infection compared to those who are uninfected, but data on perinatally HIV-infected adolescent females are lacking. Methods: Cervical cytology, HPV infection and E6/E7 mRNA were assessed in sexually active 12-24-year-old adolescent females: perinatally HIV-infected (group 1, n=40), behaviourally HIV-infected (group 2, n=10), and HIV-uninfected (group 3, n=10). Results: Median age was lower in group 1 (18 years) than in groups 2 (24 years) and 3 (20.5 years) (P<0.001), and median time since sexual debut was shorter: 2 vs 5 vs 4 years (P<0.001). More trial participants in group 1 than group 2 were on antiretrovirals (90% vs 70%; P<0.001). Abnormal cervical cytology (atypical squamous cells of undetermined significance and higher) was observed in 30% (group 1), 40% (group 2) and 30% (group 3) (P=0.92), whereas high-risk HPV infection was observed in 45%, 45% and 40%, respectively (P=1.00). Positive E6/E7 mRNA was found in 28% of group 1, but not in other groups. High-risk HPV infection predicted abnormal cytology in all groups [OR 6.77, 95% confidence interval (CI) 1.99-23.0; P=0.001). Additionally, plasma HIV RNA ≥50 copies/mL (OR 13.3, 95% CI 1.16-153.06; P=0.04) predicted abnormal cytology in HIV-infected adolescent females. Conclusions: Despite the younger age and shorter time since sexual debut, cervical cytological abnormalities and HPV infection were as common in perinatally HIV-infected as in behaviourally infected and uninfected adolescents. HPV vaccination, pre-cancer screening and antiretroviral treatment in HIV-infected female adolescents should be implemented to minimise the risk of cervical cancer.